Assessment of community-based education in community health officers' training at a Rural Medical College in Northern Ahmednagar District of Maharashtra, India: A longitudinal study - Mandar Padmakar Baviskar; Deepak B Phalke; Shubhada S Javadekar; Kalpak Kadarkar; Rajvir Bhalwar (Wolters Kluwer Medknow Publications, 2021)
We evaluated the Community Health Officer (CHO) training program in northern Ahmednagar district of Maharashtra, India. A longitudinal study was conducted among 110 CHO trainees from August 2019 to January 2020. The trainees undertook field visits and survey with lectures and clinical postings. Evaluation was based on pre- and post-Multiple Choice Question tests, the WHO Education of Health Personnel Checklist, Journals, and Logbooks. MannWhitney U-test, Wilcoxon-rank test were used to compare nonnormal variables while t-test was used for comparison of age. Initially, nursing graduates performed better than Ayurveda graduates, especially in punctuality, grasp on problems, and problem-solving ability. Nursing graduates kept better journals and logbooks. Female trainees performed better than male trainees. Ayurveda and nursing graduates were comparable at the end of the training. Need-based training and upskilling of mid-level healthcare providers can be done at scale by roping in medical colleges.